2013
DOI: 10.3906/biy-1208-44
|View full text |Cite
|
Sign up to set email alerts
|

Effect of asiatic and ursolic acids on growth and virulence factors of uropathogenic Escherichia coli strains

Abstract: This work was aimed at determining the possible antimicrobial potential of asiatic acid (AA) and ursolic acid (UA) against clinical uropathogenic Escherichia coli strains (UPECs). Phylogenetic affiliations of UPECs and virulence-associated gene carriage have been identified. PCR analysis revealed that the studied E. coli strains belong to phylogenetic group B2. All bacterial isolates were grouped into 4 pathotypes. The following were determined: the minimum inhibitory concentrations (MICs) according to CLSI; P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…To our knowledge, current work is the first report focused on the modulatory effect of the aPDT on antibacterial activity of antibiotics possessing different mechanisms of action against UPEC rods. The UPEC060 strain used in our study was genetically characterized previously and classified to phylogenetic group B2 [32]. The Ce6 used in this study is structurally closely related to porphyrins but with a higher degree of saturation of the ring system [33].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, current work is the first report focused on the modulatory effect of the aPDT on antibacterial activity of antibiotics possessing different mechanisms of action against UPEC rods. The UPEC060 strain used in our study was genetically characterized previously and classified to phylogenetic group B2 [32]. The Ce6 used in this study is structurally closely related to porphyrins but with a higher degree of saturation of the ring system [33].…”
Section: Discussionmentioning
confidence: 99%
“…32 However, the results of Horiuchi et al as well as our previous studies have shown that the MICs of AA and UA against gram-negative bacteria were higher than the MICs for gram-positive strains. [10][11][12]31 Such discrepancy is associated with the structural differences between the cell walls of these 2 types of bacteria. Gram-negative bacteria have an outer membrane with lipopolysaccharide in its outer leaflet and phospholipids in the inner leaflet.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that AA and UA change the virulence of uropathogenic Escherichia coli strains. [10][11][12] Impairment of the virulence factors decreases the pathogenicity of bacteria and thus reduces the development of infection.…”
mentioning
confidence: 99%
“…The representatives of three main classes of PT: lupanes, oleananes and ursanes are applied in the therapies of the diseases of different etiology; however, most efforts are exerted on the investigation of their anticancer [3,[6][7][8] and antibacterial properties [9][10][11]. Regarding the antibacterial properties, it was proved that the representatives of the ursane group: ␣-amyrin (AMalf) and its oxidized form ursolic acid (Urs) are effective antimicrobial agents [12][13][14]; however, the exact mechanism of their action has not been fully elucidated. Some authors claim that PT can be incorporated into the bacterial membrane, which can cause significant functional and structural alterations [15,16].…”
Section: Introductionmentioning
confidence: 99%